Effect of technological parameters on optical and mechanical properties of Spark Plasma Sintered transparent YSZ ceramics; Ceramics International; Vol. 47, iss. 8 - Paygin V. D. Vladimir Denisovich; Stepanov S. A. Sergey Aleksandrovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Alishin T. R. Timofey Ruslanovich; Valiev D. T. Damir Talgatovich (2021, 2021)
Title screen